2011
DOI: 10.1021/tx200291p
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity of Arsenic Metabolites in Human Bladder Cancer EJ-1 Cells

Abstract: The human bladder is one of the primary target organs for arsenic-induced carcinogenicity, and arsenic metabolites in urine have been suspected to be directly involved in carcinogenesis. Thioarsenicals are commonly found in human and animal urine and are also considered to be highly toxic arsenic metabolites. The present study was performed to gain insight into the toxicity and accumulation of arsenic species found in urine, including arsenate (iAs(V)), arsenite (iAs(III)), monomethylarsonic acid (MMA(V)), mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 48 publications
1
111
0
Order By: Relevance
“…In human bladder cancer cells, treatment with DMA III or DMMTA V (dimethylmonothioarsinic acid) drastically reduced GSH and p53 levels compared to control cells, while iAs also decreased p53 it was not as drastic as DMA III and treatment actually increased GSH levels compared to control. 15 One should not compare these results with the previously described study in human keratinocytes as the cancer cells have already demonstrated a compromised oncosuppresive system so further toxic insult is not likely to produce the response seen in normal cells exposed to high levels of arsenic. The…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In human bladder cancer cells, treatment with DMA III or DMMTA V (dimethylmonothioarsinic acid) drastically reduced GSH and p53 levels compared to control cells, while iAs also decreased p53 it was not as drastic as DMA III and treatment actually increased GSH levels compared to control. 15 One should not compare these results with the previously described study in human keratinocytes as the cancer cells have already demonstrated a compromised oncosuppresive system so further toxic insult is not likely to produce the response seen in normal cells exposed to high levels of arsenic. The…”
mentioning
confidence: 89%
“…11,12 Initially believed to be a detoxification mechanism, it has been realized that the organic trivalent arsenic species monomethylarsonous acid (MMA III ) and dimethylarsinous acid (DMA III ) are the most toxic of all arsenic metabolites detected in human and animal urine. [13][14][15][16][17] Variations at certain points in the human arsenic methyltransferase (AS3MT) gene may cause differences in methylating ability between individuals, 18 but data suggests a standard profile of urinary arsenic humans as 10-30% inorganic, 10-20% MMA (III+V) , and 60-80% DMA (III+V) . 19 The acute toxicity of inorganic As V has been understood in its capacity to replace phosphate in biomolecules and to uncouple ATP via so-called arsenolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thio-arsenicals are probably produced by the colon microbiota [95][96][97], and one recent study found that sulfatereducing bacteria present in the human gut was necessary for conversion of MA (V) into the thiolated monomethyl monothioarsonate [98]. Thio-arsenicals have been recognized as toxic in studies on human cells [132,133]. Thio-DMA (V), the sulphur analogue of DMA (V) and a mammalian metabolite after arsenosugar consumption [51,[134][135][136], has shown strong cytotoxic effects in cultured human lung and bladder cells [130,137].…”
Section: Mechanisms and Toxicity Of Arsenic Compounds Occurring In Sementioning
confidence: 99%
“…Among the potential sources of arsenic, we can point to water, cigarette, air pollution, glass products, and insecticides (Kiriluk et al, 2012). Arsenic in drinking water is a risk factor for BC in many parts of the world (Naranmandura et al, 2011). The chances of exposure to arsenic depends on the living conditions, such as whether they receive their drinking water from public and sanitary systems; this possibility is low in accordance with the standards defined by arsenic (Fernández et al, 2012).…”
Section: -Nutritional Factorsmentioning
confidence: 99%